Assessment of manganese- and praseodymium-substituted 5YSZ as interlayer materials for reversible solid oxide cells - Yaremchenko, Aleksey (2022)
Long-term degradation remains a major obstacle to the introduction of SOEC technology as a practical hydrogen production system. A specific degradation mechanism in SOECs is related to electrolyte deterioration and delamination phenomena at or near electrolyte/anode interface. The electrochemical studies of reversible solid oxide fuel/electrolysis cells (rSOCs) operation revealed that the degradation occurring at the electrolyte/oxygen electrode interface can be slowed down if a cell operates in a reversible SOEC/SOFC regime and that the degradation occurring in the SOEC regime may be partially recovered during the operation in SOFC mode. These observations raise prospects to halt degradation and to develop self-healing approaches based on reversible SOEC/SOFC cycles. One possible approach may be based on the introduction of redox-active components with oxygen storage capacity in the form of inclusions into the surface layer of solid electrolyte or as a thin buffer layer at the electrode/electrolyte interface capable of oxygen uptake under anodic polarization to prevent oxygen pressure build-up and reverting to oxygen loss in fuel cell mode. The present work was focused on the assessment of the impact of co-substitutions and processing conditions on the properties of ZrO2-Y2O3-MnOy and ZrO2-Y2O3-PrOy mixed oxides for prospective applicability as redox-active inclusions or buffer layers. Mn-substituted (ZrO2)0.95(Y2O3)0.05 (5YSZ) solid solutions were found to exhibit variable oxygen nonstoichiometry with manganese cations in a mixed 2+/3+ oxidation state under oxidizing conditions. Substitution by manganese gradually increases the extent of oxygen content variation on thermal/redox cycling, chemical contribution to thermal expansion and dimensional changes on reduction. It also deteriorates oxygen-ionic conductivity and improves p-type electronic conductivity under oxidizing conditions, leading to a gradual transformation from predominantly ionic to prevailing electronic transport with increasing Mn additions (5–15 mol.%). The dissolution of praseodymium oxide in 5YSZ was found to occur via the formation of pyrochlore-type Pr2Zr2O7 intermediate. Increasing PrOy additions results in a larger fraction of low-conducting pyrochlore phase which limit the total electrical conductivity. High temperature processing stabilizes the prevailing 3+ oxidation state of praseodymium cations leading to a low oxygen storage capacity. Thus, Mn-substituted 5YSZ (5–10 mol.%) is considered the most suitable for the interlayer application due to the best combination of relevant factors.